Coercive control: patterns in crimes, arrests and outcomes for a new domestic abuse offence - Brennan, Iain (The British journal of criminology, 2022)
Critics of the criminalization of coercive control warned that the criminal justice system was ill-prepared for a conceptualization of domestic abuse that relies on victim accounts of fear and manipulation rather than on evidence of violence. Using data obtained through Freedom of Information requests to police forces and aggregated police records, this paper presents police force-level and nationwide patterns in recorded crimes, police arrests and crime outcomes for this new crime and shows that, nationally, the number of recorded crimes and arrests rose steadily in its first three years, but there was significant variation in these patterns between police forces. Analysing police outcomes, we demonstrate that coercive control crimes face greater procedural challenges and are far less likely to result in prosecution than domestic abuse crimes in general. We discuss the implications of these trends and findings for the policing and criminalization of coercive control.